Pengaruh Model Pembelajaran Inkuiri Berbasis Website Terhadap Kemampuan Kognitif Siswa Kelas X Kompetensi Keahlian Multimedia Pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 2 Buduran - Karina Maulidiyah; Fitria Nur Hasanah (International Consortium of Education and Culture Research Studies, 2019)
This study was aimed to determine if there is influence of the website-based inquiry learning model on cognitive abilities of class and how much the influence of the website-based inquiry learning model has on the cognitive abilities of class X multimedia students expertise competencies in computer subjects and basic networks in SMK Negeri 2 Buduran. This research method used quantitative research methods Quasi Experimental Design with the design of